Colony dimorphism in Bradyrhizobium strains - Sylvester-Bradley, Rosemary; Thornton, Philip K.; Jones, Peter G. (1988)
Ten isolates of Bradyrhizobium spp. which form two colony types were studied; the isolates originated from a range of legume species. The two colony types differed in the amount of gum formed or size or both, depending on the strain. Whole 7-day-old colonies of each type were subcultured to determine the proportion of cells which had changed to the other type. An iterative computerized procedure was used to determine the rate of switching per generation between the two types and to predict proportions reached at equilibrium for each strain. The predicted proportions of the wetter (more gummy) or larger colony type at equilibrium differed significantly between strains, ranging from 0.9999 (strain CIAT 2383) to 0.0216 (strain CIAT 2469), because some strains switched faster from dry to wet (or small to large) and others switched faster from wet to dry (or large to small). Predicted equilibrium was reached after about 140 generations in strain USDA 76. In all but one strain (CIAT 3030) the growth rate of the wetter colony type was greater than or similar to that of the drier type. The mean difference in generation time between the two colony types was 0.37 h. Doubling times calculated for either colony type after 7 days of growth on the agar surface ranged from 6.0 to 7.3 h. The formation of two persistent colony types by one strain (clonal or colony dimorphism) may be a common phenomenon among Bradyrhizobium strains.